PERAN HUMAS DALAM MENJALIN KEMITRAN SEKOLAH DI SMA NU 1 GRESIK - Indra Pratama, Alfrinda (Inspirasi Manajemen Pendidikan, 2016)
As an educational institution, the school requires the presence of a role of public relations (PR), which can be good, or effective and efficient, because the role of public relations (PR) greatly influenced the state of a school in a way to establish good relations with the public. The main role of PR instituted education is to nurture good relations with both internal and external publics so as to create a favorable public opinion institutions or organizations, and also establish good cooperation between the school and outsiders through the participation of school public relations. The purpose of this study is to describe and analyze regarding: (1). School liaison role as a facilitator in cooperation with partner organizations in the SMA NU 1 Gresik. (2) The public relations strategy undertaken in partnership school in SMA NU 1 Gresik. This research was conducted in SMA NU 1 Gresik. The approach taken in this study is a qualitative approach to the type of case studies. This research was carried out without affecting the subject lines and the research conducted in the field. To collect the relevant data to answer the research focus, then this paper uses multiple data collection techniques, namely, interviews, observation, and documentation. The results showed that: (1). School liaison role as a facilitator in cooperation with partner organizations in the SMA NU 1 Gresik aims to foster good relations with the public, good relations arise from the communication fabric woven public relations as a facilitator in establishing the relationship. PR SMA NU 1 Gresik positioned as a bridge builder relationship as well as a forum for the exchange of information through several activities held) public relations strategy undertaken in partnership school in SMA NU 1 Gresik. In forming a strategy which is implemented as a partnership effort in school parties school publicist here doing some activities involving stakeholders in its implementation. Furthermore the publicist conduct assessments of cooperation with relevant parties in a partnership of school, and then perform the agreement or contracts with related parties through the signing of the MoU. Keywords: the role of public relations, school partnership